Partially Transparent Jaumann-Like Absorber Applied to a Curved Structure - Alireza Motevasselian; B. L. G. Jonsson (International Journal of Antennas and Propagation)
A Jaumann absorber with its metal backing replaced with a combined low-pass and polarizer FSS is investigated with respect to its absorption and its polarization-dependent low-frequency transparency properties. This structure is applied to an idealized curved wing-front end, and its monostatic radar cross-section is determined. The FSS-Jaumann structure preserves an absorption similar to the planar Jaumann absorber in the higher frequency interval and enables a partial transparency in the TEz polarization at 1 GHz. In addition, once the structure is applied to the wing-front end, a significant reduction in two-dimensional radar cross-section for both the TMz and TEz polarization over 2–16 GHz is observed. A sensitivity analysis shows that the resistivity of the inner resistive layer has a large impact on the 1 GHz transmission.